Heat transfer characteristics of supercritical water in horizontal double-pipe. (5th June 2020) - Huang, Xin; Wang, Qingqing; Song, Zichen; Yin, Yongguang; Wang, Haijun
Highlights: Studies on the heat transfer of supercritical water were conducted. Effects of variables on the heat transfer coefficients were determined. The phenomenon of the "heat transfer coefficient drift" was clarified. Abstract: In this study, the heat transfer characteristics of supercritical water in a horizontal double-pipe were investigated via experiments and numerical simulations. The influence of pressure (23 MPa, 25 MPa and 28 MPa) and mass flow rates (540 kg·h −1, 573 kg·h −1 and 604 kg·h −1 ) were studied by experiments at the inlet temperature of tube 563 K, the inlet temperature of shell varying from 626 K to 756 K. The influence of unilateral mass flow rates varying from 273 kg·h −1 to 873 kg·h −1 and the local heat transfer characteristics were studied via numerical simulations. The Shear-Stress Transport k - ω (SST) model and four selected models have been validated against experiments. The comparison suggests that Shear-Stress Transport k - ω (SST) model exhibited the best prediction. The results indicated that the effect of the pressure on heat transfer coefficients depends on bulk temperature, and the coefficients increase with the mass flow rate. When the fluid approaches pseudo-critical temperature, the heat transfer is improved. Nevertheless, the peak heat transfer coefficient occurs at a bulk temperature that is slightly higher than the pseudo-critical point. This phenomenon is strongly correlated with the specific heat of the near-wall fluid, and it is mainly caused by a temperature imbalance between the bulk and the near-wall fluid of the shell side. The imbalance is due to a significant bulk temperature difference between the tube and the shell or a small mass flow rate of the shell side. Finally, the overall value of the local heat transfer coefficient is determined by the fluid temperature of the near-wall region.